NASOPHARYNGEAL CARRIAGE OF STREPTOCOCCUS PNEUMONIAE IN ORPHANS, PRESCHOOL CHILDREN AND UNORGANIZED CHILDREN UNDER 5 YEARS - M. A. Lazareva; T. V. Kulichenko; N. M. Alyab'eva; O. A. Ponamarenko; A. V. Lazareva; L. K. Katosova; N. A. Mayanskii (Вопросы современной педиатрии, 2015)
Nasopharyngeal colonization with Streptococcus pneumoniae is a source of respiratory mucosal and invasive infections. For effective vaccine prophylaxis of these diseases the national monitoring of the circulating serotypes and antimicrobial resistance of Streptococcus pneumoniae is required. Objective: To analyze serotype diversity and antimicrobial resistance of S. pneumoniae in the nasopharyngeal carriage in children under 5 years. Methods and patients: The study included orphanage, nursery and children not attending preschool institutions (unorganized children) without respiratory infections and not receiving antibiotic therapy. Conducted microbiological analysis of nasopharyngeal flora, serotyping of pneumococcus, assess their sensitivity to antibiotics. Results: Nasopharyngeal carriage of S. pneumoniae was found in 23%, Moraxella catarrhalis - in 23%, Haemophilus influenzae - 16% of the 246 children included in the study. Serotype was determined in 54 pneumococcal isolates: predominant serotypes 19F (21%), 6B (15%), 23F (14%), 14 (8%). The coincidence of the spectrum obtained with serotypes members of the PCV7 pneumococcal conjugate vaccines and PKV10, was 81% in PKV13 - 90%. The proportion of strains sensitive to clindamycin, 31%, to macrolides - 40% to trimethoprim / sulfamethoxazole - 60%. Multiple resistance was observed in 37% of the identified pneumococcal serotypes. In erythromycin-resistant strains resistance was caused by the presence of ermB-gene (in 74% of cases) or mef-dependent efflux pump as the sole determinant (9%), in 17% of cases – with its association. Maximum antibiotic resistance is observed in pneumococcal vaccine serotypes. Conclusions: The results of the study comparing with previously obtained data shows stability over the past decades the spectrum of pneumococci circulating in the Russian population of children. A substantial increase in pneumococcal resistance to (especially vaccine serotypes) antibiotic penicillin, macrolides, clindamycin is observed.